Effect of stage duration on physiological variables commonly used to determine maximum aerobic performance during cycle ergometry - Roffey, D. M.; Byrne, N. M.; Hills, A. P. (Journal of Sports Sciences, 2007)
In this study, we examined the effect of stage duration on physiological variables commonly used to determine maximum aerobic performance during cycle ergometry. Ten recreationally trained males (mean age 27.8 ± 7.1 years; BMI 24.3 ± 2.5 kg · m-2; VO2max 52.5 ± 5.9 ml · kg-1 · min-1) performed three different stage duration protocols on two separate occasions. Each short stage (SS; 1-min stages), long stage (LS; 3-min stages), and constant load + short stage (CL + SS; 4-min constant load followed by 1-min stages) protocol started at 50 W with increments of 30 W. The physiological variables measured included: time to maximum, maximum workload, maximum oxygen consumption (VO2max), maximum heart rate, maximum rating of perceived exertion, maximum blood lactate concentration, and maximum respiratory exchange ratio. The ventilatory threshold was calculated for every trial of the three protocols. There was no difference in VO2max, but maximum heart rate was higher in the LS protocol (P<0.05). Maximum respiratory exchange ratio varied between the protocols (P<0.05), while maximum workload differed between the SS and LS protocols, and the LS and CL + SS protocols (P<0.0001). The physiological variables were comparable between trials for the SS and CL + SS protocols, but maximum workload and O2max differed for the LS protocol (P<0.05). Workload at the ventilatory threshold was lower for the LS protocol (P<0.05). Heart rate at the ventilatory threshold was different between the LS and CL + SS protocols (P<0.05). Performing a test involving 1- or 3-min stage durations on a single occasion was appropriate for the determination of VO2max and the ventilatory threshold. However, the disparity in heart rate and workload could result in differences in mechanical and physiological work being undertaken. Consistent use of a protocol may alleviate errors during exercise prescription.